Analisis Rasio Keuangan untuk Menilai Kinerja Pengelolaan Keuangan Daerah Kabupaten Jepara Tahun Anggaran 2013-2015 - Meri Alfiani Saputri; Solikul Hidayat (Jurnal Rekognisi Akuntansi, 2017)
To assess the performance of the Regional Government (Pemda) in managing their regional finances, among others, by conducting a financial ratio analysis on the local government's financial statements. The results of the financial ratio analysis are then used as a benchmark in assessing the level of independence, efficiency, effectiveness, harmony and growth. The data used in this study are the financial statements of the Jepara Regency Government in 2013, 2014 and 2015. Furthermore, the data will be analyzed using five financial ratios, namely: the independence ratio, the effectiveness ratio, the harmony ratio, the efficiency ratio and the growth ratio. The results of data analysis state that the financial performance of the Jepara Regency Government which is still lacking is the aspect of independence and the aspect of harmony, because the ratio of independence is 10.68% (2013), 16.95% (2014) and 16.37% (2015), while the ratio operational expenditure to the Regional Budget of 854.57% (2013), 546.64% (2014) and 495.22% (2015). On the other hand, the ratio of capital expenditure to APBD is also still low compared to operational expenditure, which is 118.70% (2013), 81.55% (2014) and 122.26% (2015). The level of efficiency and effectiveness of the Jepara Regency Government in managing funds is very efficient and effective, because the effectiveness ratio is 112.49% (2013), 123.23% (2014) and 124.37% (2015) while the efficiency ratio is 2.25 % (2013), 1.72% (2014), and 2.20% (2015). PAD growth was quite high in 2014 amounting to 73.18% but for 2015 it was only 16.65%, for income growth it increased by 15.34% (2014) and 20.72% (2015). On the other hand, operating expenditure increased by 10.78% (2014) and 5.68% (2015) and capital expenditure increased by 18.97% (2014) to reach 74.90% (2015). The Jepara Regency Government is expected to strive to further increase its PAD by optimizing resource management and expanding sectors that have the potential to increase PAD, so that dependence on revenues from the Central Government can be reduced. The Jepara Regency Government should be more proportional in allocating its expenditures, namely reducing operational expenditures and increasing capital expenditures.